Synthesis and Characterization of Polyfumarateurethane Nanoparticles for Sustained Release of Bupivacaine - Soo-Yong Park; Jiin Kang; Ji-Young Yoon; Ildoo Chung (MDPI AG, 2020)
Biodegradable polyfumarateurethane (PFU) for use as a bupivacaine delivery vehicle, synthesized using di-(2-hydroxypropyl fumarate) (DHPF), polyethylene glycol (PEG) and 1,6-hexamethylene diisocyanate (HMDI), was designed to be degradable through the hydrolysis and enzymatic degradation of the ester bonds in its polymer backbone. Using a water-in-oil-in-water double emulsion techniques, nanoparticles encapsulating water or fluorescein isothiocyanate (FITC) were fabricated to avoid the immune system owing to the presence of PEG on their surface. The morphologies of these nanoparticles were characterized by DLS, TEM, FE-SEM, and fluorescent microscopies. The present study explored the encapsulation, loading efficiency and in vitro drug release of bupivacaine encapsulated with biodegradable PFU nanoparticles for the treatment of local anesthesia. Various concentrations of bupivacaine were encapsulated into nanoparticles and their encapsulation efficiencies and drug loading were investigated. Encapsulation efficiency was highest when 2.5% bupivacaine was encapsulated. Drug release behavior from the bupivacaine-loaded PFU nanoparticles followed a sustained release profile.